Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Tulungagung - Nuning Sunu Tri Rahayu; Ratna Dewi Mulyaningtiyas (Otonomi, 2023)
The purpose of this research among others to know the quality of public services to the community satisfaction in city population and civil registration Tulungagung district. This research methodology used a quantitative approach with the kind of research descriptive quantitative. Data gathered by the survey respondents to 30.Sample determined by using techniques of sampling saturated. The linear regression analysis data using multiple with the help of the ibm spss statistic 26,0 for windows programs. In this research variable service quality public classified in the tangibles 5 dimensions, reability, responsiveness, assurance and emphaty. The result showed significant impact on public service quality community satisfaction. Dimension the quality of the public services, the most commonly known among responsiveness to the other four dimensions.